(untitled) (Itinera, 2018)
In the present article, I intend to examine the importance of Engel’s mimicry for the corporeal visualization of affects, showing the links with its roots in the early German Enlightenment. If the body serves as a picture of the soul, the aim of this essay is to understand how Engel’s mimicry turns this correspondence to its own purpose, enhancing its role as a privileged observatory of the human mind as well as a building site of a historical form of humanity.